Identity preserved plant molecular farming offers value-added opportunity for farmers - Kunkler, Kyle; Gerlt, Scott (Frontiers in Plant Science, 2024)
Bulk commodity row crop production in the United States is frequently subject to narrow profit margins, often complicated by weather, supply chains, trade, and other factors. Farmers seeking to increase profits and hedge against market volatility often seek to diversify their operations, including producing more lucrative or productive crop varieties. Recombinant plants producing animal or other non-native proteins (commonly referred to as plant molecular farming) present a value-added opportunity for row crop farmers. However, these crops must be produced under robust identity preserved systems to prevent comingling with bulk commodities to maintain the value for farmers, mitigate against market disruptions, and minimize any potential food, feed, or environmental risks.